The Influence of Placebo Effect on Craving and Cognitive Performance in Alcohol, Caffeine, or Nicotine Consumers: A Systematic Review - Galindo, María Nerea; Navarro, José Francisco; Cavas, María (Frontiers in Psychiatry, 2020)
Abstract Objective: The present systematic review aims to analyze the evidence about the influence of placebo effect on craving and cognitive performance in alcohol, caffeine, and nicotine consumers. ¬Methods: Relevant studies were identified via Pubmed, Web of Science, and Scopus databases (up to March 2020). Only those papers published between 2009 and 2019 were searched. Results: Of the 115 preliminary papers, 8 studies of database search and 9 of the manual search were finally included in this review. Findings showed that while alcohol expectancies increased craving, caffeine and nicotine expectancies tend to decrease it. Alcohol expectancies caused similar or slower reaction time when alcohol was not consumed, impairments on inhibitory control (especially after alcohol consumption) and similar post-error slowing. The effect of caffeine and nicotine on reaction time has not been elucidated yet, however, caffeine expectancies have been shown to improve accuracy and the attentional filtering of distracting stimuli. Conclusions: Alcohol, caffeine, and nicotine expectancies play an important role on craving. Although expectancies produce an effect on cognitive performance, caffeine and nicotine beliefs show an ambiguous impact on reaction time. Only the influence of alcohol expectancies on reaction time has been clarified. Furthermore, caffeine beliefs enhance accuracy.